2008
DOI: 10.1152/ajpregu.00606.2007
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin and NMDA receptors in the median preoptic nucleus mediate hemodynamic response patterns to stress

Abstract: The brain renin-angiotensin system plays an important role in the regulation of arterial pressure in response to stress, in part due to activation of AT1 receptors in the hypothalamic median preoptic nucleus (MnPO) by endogenous angiotensin II (ANG II). N-methyl-d-aspartate (NMDA) receptors are also involved in the angiotensinergic signaling pathway through the MnPO. We investigated whether AT1 and NMDA receptors in the MnPO are responsible for variable hemodynamic response patterns to stress. Cocaine or start… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
9
1
Order By: Relevance
“…Both the nucleus accumbens (Westbrook et al, 1997;Pezze and Feldon, 2004;Martinez et al, 2008) and septal nucleus (Beck and Fibiger, 1995;Sparks and LeDoux, 1995;Calandreau et al, 2007;Reis et al, 2010) have at times been implicated in contextual conditioning, even though their exact roles remain unclear. The preoptic area seems to play a role in defensive and anxious behaviors (Briski and Gillen, 2001;McGregor et al, 2004;Salomé et al, 2004;Schwartz et al, 2008), but we found no studies providing direct evidence for its involvement in contextual conditioning.…”
Section: Discussioncontrasting
confidence: 62%
“…Both the nucleus accumbens (Westbrook et al, 1997;Pezze and Feldon, 2004;Martinez et al, 2008) and septal nucleus (Beck and Fibiger, 1995;Sparks and LeDoux, 1995;Calandreau et al, 2007;Reis et al, 2010) have at times been implicated in contextual conditioning, even though their exact roles remain unclear. The preoptic area seems to play a role in defensive and anxious behaviors (Briski and Gillen, 2001;McGregor et al, 2004;Salomé et al, 2004;Schwartz et al, 2008), but we found no studies providing direct evidence for its involvement in contextual conditioning.…”
Section: Discussioncontrasting
confidence: 62%
“…Pharmacological inhibition of AT 1 or NMDA receptors within the MnPO reduces the vasoconstrictor responses to cocaine or ice cold startle in a subgroup (vascular responders) of Sprague–Dawley rats, showing a role for the MnPO in stress‐mediated hemodynamic responses (Schwartz et al . ). Further, there is evidence to show that the MnPO relays signals from angiotensin‐sensitive neurones in the subfornical organ to the PVN (Tanaka et al .…”
Section: Cardiovascular Regulationmentioning
confidence: 97%
“…Several hypothalamic and brain stem regions associated with autonomic regulation have been implicated in the central pressor actions of AngII during stress. Microinjection of losartan and saralasin directly into anterior and dorsomedial hypothalamic nuclei reduced the pressor and sympathoexcitatory effects of various psychological stressors in rats 21,24,25 . Similarly, microinjection of the highly specific AT 1 receptor antagonist candesartan into the dorsomedial hypothalamus (DMH) dose‐dependently reduced the pressor effect of air‐jet stress in rabbits 26 .…”
Section: Angiotensin II and Aversive Stressmentioning
confidence: 97%
“…Microinjection of losartan and saralasin directly into anterior and dorsomedial hypothalamic nuclei reduced the pressor and sympathoexcitatory effects of various psychological stressors in rats. 21,24,25 Similarly, microinjection of the highly specific AT 1 receptor antagonist candesartan into the dorsomedial hypothalamus (DMH) dose-dependently reduced the pressor effect of air-jet stress in rabbits. 26 It is conceivable that AngII is also an important stress mediator in the rostral ventrolateral medulla (RVLM), a region that is critically implicated in sympathetic regulation 27 and that contains a high density of AT 1 receptors.…”
Section: Psychoemotional Stressorsmentioning
confidence: 99%